A new species of Tychus Leach, 1817 from Lebanon (Coleoptera, Staphylinidae, Pselaphinae) - Sabella, Giorgio; Viglianisi, Fabio Massimo; D’urso, Vera (Zootaxa, 2019)
Tychus meggiolaroi sp. n. from Lebanon is described and illustrated. It belongs to the Tychus cilicicus species group (Sabella & Kurbatov 2002) and can be readily distinguished from related taxa by the different structure of the aedeagus and morphological features of antennae.